2017
DOI: 10.1111/jocd.12438
|View full text |Cite
|
Sign up to set email alerts
|

New soft tissue filler derived from autologous keratin and fibroblast for neck wrinkles

Abstract: Autologous keratin and fibroblast as soft tissue filler is an effective treatment option for neck rejuvenation with long-term efficacy for reversing of skin aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…In our previous study, this tissue-engineering filler performed well in correction of neck wrinkles, tear trough deformity, and facial scars and showed a long-time effect. 18,19,28 In this study, autologous keratin and fibroblasts were injected for static forehead rhytides correction, and the curative effect was very well. The static forehead rhytides were significantly improved within 6 months after injection, and at 24th month, there are also 91% patients showed good result, which means autologous fibroblasts and keratin have a long-term and satisfied amelioration.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In our previous study, this tissue-engineering filler performed well in correction of neck wrinkles, tear trough deformity, and facial scars and showed a long-time effect. 18,19,28 In this study, autologous keratin and fibroblasts were injected for static forehead rhytides correction, and the curative effect was very well. The static forehead rhytides were significantly improved within 6 months after injection, and at 24th month, there are also 91% patients showed good result, which means autologous fibroblasts and keratin have a long-term and satisfied amelioration.…”
Section: Discussionmentioning
confidence: 92%
“…8 Unfortunately, BTX-A and HA will lose effect in about 6 months and repeat injection, which became the main complain of the patinets. 18 Autologous cultured fibroblasts were accepted and used in clinical gradually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Martínez et al (2016) showed that the wound healing rate of chronic leg ulcers can be increased by using hairy punch grafts. Autologous fibroblasts have been used as filler material for the nasojugal groove to correct wrinkles ( Moon et al, 2018 ) and with keratinocytes have been used for neck wrinkles ( Wang et al, 2018 ). For the gingival recession studies, collagen scaffolds with autologous fibroblast could not promote a statistically significant change ( Milinkovic et al, 2015 ).…”
Section: Clinical Uses Of Mesenchymal Stromal Cells and Fibroblastsmentioning
confidence: 99%
“…Many cosmetic options exist to address the single signs of neck aging individually, but little literature exists about the safety and efficacy of combining such procedures and devices. Possible therapeutic strategies include the following: intense pulsed light, ablative and nonablative fractional lasers, microfocused ultrasound, radiofrequency, cryolipolysis, deoxycholic acid, neuromodulators, hyaluronic acid (HA) dermal fillers, calcium hydroxyapatite and the so‐called “Nefertiti lift,” which consists of injecting the platysmal bands and the inferior border of the mandible with botulinum toxin . Recently published articles stressed the importance of combining those strategies .…”
Section: Introductionmentioning
confidence: 99%